The Impact of Macroeconomic Factors on Stock Performance in the International Capital Market - Tarigan, Johanes Prasetia; Pangestu, Yogi; Rizki, M. (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study examines the impact of macroeconomic factors—specifically inflation, interest rates (BI Rate), and the rupiah exchange rate—on stock performance in the global capital market. Through rigorous statistical analysis, the research explores the relationships between these economic indicators and stock price movements across various international stock exchanges. The results offer valuable insights for investors and capital market practitioners, helping them anticipate risks and make more informed investment decisions amid the ever-changing dynamics of the global economy.